Crystal structure of 2-(adamantan-1-yl)-5-(3,5-dinitrophenyl)-1,3,4-oxadiazole, C18H18N4O5 - Al-Wahaibi, Lamya H.; Blacque, Olivier; Tiekink, Edward R. T. *; El-Emam, Ali A. (De Gruyter, 2022)
C18H18N4O5, monoclinic, P21/c (no. 14), a = 11.7553(8) Å, b = 6.4876(4) Å, c = 22.3442(15) Å, β = 91.263(7)°, V = 1703.64(19) Å3, Z=4, Rgt(F) = 0.0531, wRref(F2) = 0.1376, T = 160 K. CCDC no.: 2173380 The molecular structure is shown in the figure. Table 1 contains crystallographic data and Table 2 contains the list of the atoms including atomic coordinates and displacement parameters.